CORRELATION OF APOLIPOPROTEIN B LEVELS WITH THE DEGREE OF CORONARY ARTERY STENOSIS IN CHRONIC CORONARY SYNDROME PATIENTS - Muhammad Novran Chalik; Erwin Sukandi; Irfannuddin; Syamsu Indra; Zen Ahmad (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Apolipoproteins are structural components of plasma lipoproteins that involved in lipoprotein metabolism and lipid transport, reflect the number of circulating atherogenic particles. This study aims to investigate the correlation between serum apolipoprotein B levels and the degree of coronary artery stenosis in patients with chronic coronary syndrome. A cross-sectional study design was used, involving 34 patients selected from a total population of 69 individuals. Data were collected from July 2024 to September 2024. The results showed that most respondents had elevated apolipoprotein B levels, with a mean value of 141.41 ± 25.06 mg/dL, and SYNTAX score of ≥ 23, with a mean value of 24.09 ± 2.69. Pearson’s correlation test indicated a significant relationship between apolipoprotein B levels and SYNTAX scores (p = 0.029, r = 0.376). Multivariate analysis revealed a significant p-value for apolipoprotein B (p = 0.017) with a positive regression coefficient.